Māori Becoming Peer Educators in Later Life: Impacts on Identity, Well-being, and Social Connectedness. (10th June 2020) - Simpson, Mary Louisa; Oetzel, John; Nock, Sophie; Greensill, Hine-iti-moana; Meha, Pare; Reddy, Rangimahora; Johnston, Kirsten; Cameron, Michael; Harding, Truely; Shelford, Pita; Smith, Linda Tuhiwai; Hokowhitu, Brendan
Abstract: Objective: The aim of this study was to examine ways that older Māori (New Zealand's Indigenous people) enhanced their ability to be peer educators and how this role impacted on their sense of purpose and well-being in later life. Method: Kaupapa Māori and community-based participatory research principles guided the peer intervention involving 26 Māori kaumātua (older people 55 years and older) as peer educators (tuakana) for 121 other kaumātua (teina) facing transitions in later life. Each pair held up to 3 conversations; independent coders rated tuakana communication skills. We used mixed methods in a pre- and post-test, clustered staggered design. Participants completed baseline and post-intervention assessments of health and well-being consistent with Māori worldviews. 5 focus groups involving 22 teina and 1 with 5 tuakana were held. Results: Tuakana communication skills were rated as high by teina and independent coders. Qualitative analysis supported the importance of Māori communication processes for the role. Further, three measures increased significantly from the baseline to the final period for tuakana accounting for about 15% of the variance in these variables: sense of purpose ( p = .07), self-rated health ( p = .05), and health-related quality of life ( p = .04). The qualitative analysis supported the benefits of the peer educator role for older Māori including enhanced sense of identity, well-being, and social connectedness. Discussion: The results demonstrated that kaumātua had strong communication in the peer educator role and that the intervention has positive impacts for them. The study contributes to peer intervention research that may help to improve experiences ofIndigenous and other older people.